Identification of a new Clostridium perfringens variant with a chromosomally encoded enterotoxin gene in a suspected persistent food poisoning outbreak in Eritrea - Lahti, Päivi; Jaakkola, Kaisa; Hörman, Ari; Heikinheimo, Annamari; Sovijärvi, Ava; Korkeala, Hannu (Frontiers in Microbiology, 2024)
Clostridium perfringens is a causative agent of various human and animal enteric diseases including food poisoning. Here we describe an interesting case of a persistent food poisoning outbreak amongst Finnish peacekeepers in Eritrea, possibly caused by Clostridium perfringens carrying a new variant of chromosomally encoded enterotoxin gene. C. perfringens strains causing food poisoning carry the enterotoxin gene, cpe, in its chromosome (c-cpe) or on a plasmid (p-cpe). PCR assays are widely used to toxinotype C. perfringens strains. The integration sites for the cpe gene are highly conserved and PCR assays targeting the cpe gene and the adjacent IS elements (the IS1470 in c-cpe and the IS1470like or IS1151 in p-cpe strains) are used to further determine the genetic location of the cpe gene.We sequenced nine enteropathogenic C. perfringens strains related to a persistent food poisoning outbreak among Finnish peacekeepers in Eritrea. Six of these strains produced non-typeable cpe results in the standard PCR assay due to divergence in the enterotoxin integration site. The gene order of the new variant of the chromosomal cpe insertion site with an additional IS1470 element impairing genotyping PCR assay for the location of cpe is described. In addition, variant c-cpe strains carried 58 to 81 copies of IS1470 in their genomes, compared to 9 to 23 copies found in previously described c-cpe strains. Thus, the present study represents an untraditional type of C. perfringens food poisoning caused by variant c-cpe strains, and the sequenced strains bring geographic variation to the existing strain collection of sequenced C. perfringens.